Գեղագիտական հարաբերությունը մաթեմատիկայի ուսուցման գործընթացում - Միքայելյան, Համլետ (Զանգակ հրատ.)
В работе рассматриваются эстетические отношения как частный случай бинарных и тернарных отношений. Выявляются некоторые особенности тернарных эстетических отношений. Обсуждается проблема создания здоровых положительных эстетических отношений в процессе преподавания математики, выявляется субъективность роли учашегося и особенность роли учителя в эстетических взаимоотношениях. In this paper we consider the aesthetic attitude as a special case of binary and ternary relations. The article identifies some of the features of ternary aesthetic relations. It investigates problem of creating a healthy, positive aesthetic relations in the teaching of mathematics, showing the role of subjective pupils’ health and especially the role of the teacher in the aesthetic sense.
Keywords: Ուսուցման և դասավանդման մեթոդիկա